Evaluating international student experiences in a short-term mobility program: A case of the Delightful Istanbul Program - Irali, Ali Efe; Erguven, Mine; Armani, Arta (Journal of International Students, 2026)
Short-term international academic programs are increasingly adopted to promote global engagement in higher education; however, student experiences within these initiatives remain underexplored. This study evaluates the academic perceptions of 129 international students who participated in the 2024 Delightful Istanbul Summer Program at Istanbul Aydin University. Data were collected using the validated Course Experience Questionnaire (CEQ), and analyses conducted with SPSS confirmed high internal reliability (α=.80-.92). Among CEQ dimensions, Good Teaching received high ratings, particularly from Health Sciences students (M=4.63), while Emphasis on Independence received lower ratings, particularly from STEM students (M=3.66). No significant gender differences emerged. Health Sciences students scored significantly higher than both STEM and Social Sciences students in Generic Skills (p=.004). Field-of-study differences were also found in Good Teaching (p=.039) and Overall Satisfaction (p=.003), with Health Sciences reporting the highest means. Across course types, significant variations appeared in teaching quality (p<.01), skill development (p<.001), independence (p<.05), and overall satisfaction (p=.002), favoring STEM and Health Sciences courses. Regression analysis identified Good Teaching (β=.50, p<.001) and Generic Skills (β=.21, p=.003) as significant predictors of overall satisfaction, explaining 57% of the variance. These findings highlight the value of well-structured, interdisciplinary short-term programs in enhancing student engagement and learning outcomes.